The Effect of Compensation, Work Motivation, and Work Discipline on Employee Performance of PT Pabrik Gula Candi Baru Sidoarjo - Bahri, Muhammad Fajrul Yusuf; Prabowo, Budi (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
This study aims to determine and analyze the effect of compensation, work motivation, and work discipline on employee performance at PT. Pabrik Gula Candi Baru, Sidoarjo. The type of research used is associative with a quantitative approach. In this study, the simple random sampling technique was applied to obtain 60 samples from 150 employees in the company. Data analysis was carried out using multiple linear regression analysis with SPSS software. The analysis results showed that work discipline was the variable that most influenced performance. The results of SPSS data processing showed that: 1) compensation variables (X1), work motivation (X2), and work discipline (X3) simultaneously had a significant effect on employee performance (Y) at PT. Pabrik Gula Candi Baru, Sidoarjo; 2) compensation variables (X1) partially did not have a significant effect on employee performance (Y); 3) work motivation variables (X2) partially also did not have a significant effect on employee performance (Y); and 4) work discipline variables (X3) partially had a significant effect on employee performance (Y).